Complication of Conventional Septoplasty - Ahmady Roozbahany, Navid; Khajavi, Mehdi; Abbaszadeh, Hojjat-allah (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2015)
Background: Septoplasty is one of the most commonly performed operations with several complications. Purpose: To categorize and demonstrate the probability of the occurrence of septoplasty complications. Methods: Three hundred and twelve patients who underwent septoplasty in Loghman Hakim general hospital, Tehran, Iran, were followed up for 6 months and evaluated for probable post-operative complications. Results:The most common complication was remained deviation which was observed in 26.2% of patients followed by synechiae and perforations. There was no case of serious and life threatening complications. Conclusion: Septoplasty has both aesthetic and functional complication. However, meticulous and careful surgery can prevent most of them.